CAR-T cell therapy for hepatocellular carcinoma: current trends and challenges - Zhou, Yexin; Wei, Shanshan; Xu, Menghui; Wu, Xinhui; Dou, Wenbo; Li, Huakang (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) ranks among the most prevalent cancers worldwide, highlighting the urgent need for improved diagnostic and therapeutic methodologies. The standard treatment regimen generally involves surgical intervention followed by systemic therapies; however, the median survival rates for patients remain unsatisfactory. Chimeric antigen receptor (CAR) T-cell therapy has emerged as a pivotal advancement in cancer treatment. Both clinical and preclinical studies emphasize the notable efficacy of CAR T cells in targeting HCC. Various molecules, such as GPC3, c-Met, and NKG2D, show significant promise as potential immunotherapeutic targets in liver cancer. Despite this, employing CAR T cells to treat solid tumors like HCC poses considerable challenges within the discipline. Numerous innovations have significant potential to enhance the efficacy of CAR T-cell therapy for HCC, including improvements in T cell trafficking, strategies to counteract the immunosuppressive tumor microenvironment, and enhanced safety protocols. Ongoing efforts to discover therapeutic targets for CAR T cells highlight the need for the development of more practical manufacturing strategies for CAR-modified cells. This review synthesizes recent findings and clinical advancements in the use of CAR T-cell therapies for HCC treatment. We elucidate the therapeutic benefits of CAR T cells in HCC and identify the primary barriers to their broader application. Our analysis aims to provide a comprehensive overview of the current status and future prospects of CAR T-cell immunotherapy for HCC.